Kant, Anthropocentrism, and Animal Welfare - Wilson, Holly L. (Con-Textos Kantianos. International Journal of Philosophy, 2023)
Abstract: This paper will argue six reasons why Kant is an anthropocentric, but not an anthropo-supremacist. It will lay out Kant’s case against animal egalitarianism, and how Kant’s moral theory nevertheless provides sufficient obligations not to be cruel to other animal species and to care about their welfare. This paper will show how Kant’s moral theory will apply in concrete detail with one species of non-human animal, namely the dairy cow. A dairy farmer who is also motived by Kantian virtue will have enough moral incentive to care about their dairy cows even though Kant’s duties to other animal species are indirect and not direct.